O corpo: experiência da realidade; material de experimentação e criação na tatuagem - Oliveira, Sabrina de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The present work seeks to establish reflections and connections about the thought of what a body is and how it perceives and acts on the real and changes, based on Merleau Ponty's "Phenomenology of Perception" and the concept of Deleuzian becoming, in particular through reading from “The unreconciled time” by Peter Pál Pelbart, creating parallels with the body modification/tattoo and its artistic character. It also discusses in its second stage performance works with modification and contemporary authorial tattooing, which are part of a vision of anti-art and have the body as material. The tattoo scenario has undergone changes throughout its history, and some are analyzed in the study of contemporary authorial tattooing, also presenting a relevant space for research, which is the Tattoo Study Group, which brings together tattoo artists in order to research and discuss the practice. In parallel, it follows the practical production of the performance experiment .estudo do Todo., which motivated the research, and other tattoo performance proposals, in addition to the authorial tattoo work.

O presente trabalho procura estabelecer reflexões e conexões acerca do pensamento do que é um corpo e como percebe e age sobre o real e se modifica, a partir da “Fenomenologia da Percepção” de Merleau Ponty e do conceito do devir deleuziano, em particular pela leitura de “O tempo não-reconciliado” de Peter Pál Pelbart , criando paralelos com a modificação corporal/tatuagem e seu caráter artístico. Discorre também em sua segunda etapa trabalhos de performance com modificação e a tatuagem autoral contemporânea, que se inserem em uma visão de anti arte e têm o corpo como material. O cenário da tatuagem sofreu mudanças ao longo de sua história, e algumas são analisadas no estudo da tatuagem autoral contemporânea, apresentando também um espaço relevante para a pesquisa, que é o Grupo de Estudos de Tatuagem, que reúne tatuadores no intuito de pesquisar e discutir a prática. Em paralelo, segue a produção prática do experimento performático .estudo do Todo.,que motivou a pesquisa, e outras propostas de tattoo performance, além do trabalho de tatuagem autoral.
The body: experience of reality; experimentation and creation material in tattooing
Keywords: Corpo como suporte da arte; Performance (Arte); Tatuagem; Marcas corporais